80.1k views
1 vote
1. 3x + 6y = 3 and 7x + 3y = 7
ons for bo​

2 Answers

5 votes

Answer:

x = 1

y = 0

Explanation:

3x + 6y = 3

7x + 3y = 7

=> 3y = 7 - 7x

=> y = -7/3x + 7/3

3x + 6(-7/3x + 7/3) = 3

=> 3x - 14x + 14 = 3

=> -11x = -11

=> -x = -11/11

=> -x = -1

=> x = 1

So, 3(1) + 6y = 3

=> 3 + 6y = 3

=> 6y = 0

=> y = 0/6

=> y = 0

So, x = 1

y = 0

User Sadegh Saati
by
5.3k points
6 votes

Answer:

(1,0)

Explanation:

3x + 6y = 3

7x + 3y = 7

Multiply the second equation by -2

-2( 7x + 3y = 7)

-14x -6y = -14

Add this to the first equation to eliminate y

3x + 6y = 3

-14x -6y = -14

--------------------

-11 x = -11

Divide by -11

x = 1

Now find y

3x + 6y = 3

3 +6y = 3

Subtract 3 from each side

6y = 0

y =0